Spatiotemporal pattern of the incidence of tuberculosis and associated factors - George Jó Bezerra Sousa; Geraldo Lucas Alves Monte; Davi Gomes Sousa; Thatiana Araujo Maranhão; Maria Lúcia Duarte Pereira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective To analyze the spatiotemporal pattern of tuberculosis incidence and its associated factors. Methods: Ecological study, which used tuberculosis notifications during 2001-2017 and as units of analysis the municipalities of the state of Ceará of the Notifiable Diseases Information System. Time pattern analysis techniques and geographically weighted regression were used. Results: The gross incidence rate in the state reached a peak of 226.1/100 thousand inhabitants with a significant decrease of 1.9% per year (95%CI −3.0-−0.7). The main clusters were identified in Fortaleza and its metropolitan region, as well as in the Sobral region. The socioeconomic indicators that were associated with the incidence were: occupation in the agricultural sector and services, population in households with bathrooms and running water and vulnerable to poverty. Conclusion: There was a significant decrease in the incidence of the disease in the state of Ceará. The spatial clusters were mostly located in areas with high population and the indicators most related to the formation of spatial clusters were related to employment/income, housing and vulnerability.